RANCANGAN BANGUN SISTEM PENDAFTARAN SISWA BARU SMK CITRA NEGARA DEPOK MENGGUNAKAN METODE WATERFALL - Trisna Wahyudi Rohman; Phita Pitria; Aprilia Styanigrum; Arbi Sarmembi; Selestina Didi Irmaya (CV. Denasya Smart Publisher, 2025)
The rapid development of information and communication technology has revolutionized various sectors, including education. In response to the challenges of manual registration processes, SMK Citra Negara Depok initiated the design of a modern, integrated online student registration system using the Waterfall method. This research aims to enhance efficiency, improve data accuracy, and provide better access for prospective students. Through qualitative and quantitative approaches, this study analyzes existing problems, designs solutions, and evaluates the system’s effectiveness. The results demonstrate that the proposed system significantly optimizes registration processes, thereby increasing the institution's competitiveness in the digital era.